Infiltration-Friendly Land Uses for Climate Resilience on Volcanic Slopes in the Rejoso Watershed, East Java, Indonesia - Suprayogo, D.; Widianto; Hairiah, K.; Meilasari, N.; Rabbani, A.L.; Ishaq, R.M.; Noordwijk, M. van (Copernicus GmbH, 2020)
Forest conversion to agriculture or agroforestry may increase risks of loss of hydrologic functions in an era of climate change. Infiltration during high-intensity rainfall is important for avoiding erosion and feeding aquifers but depends on land use practices that maintain soil macroporosity. In the forest-to-open-field-agriculture continuum it is not clear where thresholds to functionality (degradation) are crossed. Our assessment of infiltration-friendly land uses in the Rejoso watershed on the slopes of the Bromo volcano in East Java (Indonesia) focused on two zones, upstream (above 800 m a.s.l.) and midstream (400–800 m a.s.l.) of the Rejoso river and feeding aquifers that support lowland rice areas as well as drinking water supplies to nearby cities. Upstream land uses included old and young pine plantations (production forest) and highland vegetable crops with variation of tree canopy cover. Midstream land uses included production forest, multistrata coffee-based agroforestry, clove-based agroforestry, and several mixed agroforestry types with variation of tree canopy cover. We quantified infiltration and erosion in 3 replications per land use category over a 3-month period (one-third of mean annual rainfall), with 6–13 % of rainfall with intensities (51–100 mm day−1). We related infiltration rates to plot-level characteristics across the land use systems and found statistically significant relations with tree canopy cover (likely based on combined effects of interception, preceding water use and effects on soil), understory cover, amount of litter, and soil surface roughness. Results for the upstream watershed showed that a tree canopy cover > 55 % is associated with adequate infiltration and acceptable soil erosion levels. For vegetable cultivation in steep (45–65 %) to very steep (> 65 %) lands with a tree canopy cover below 55 %, surface runoff was between 24 % and 46 % of rainfall, with high rates of soil erosion. Midstream, a tree canopy cover of > 80 % was associated with infiltration-friendly land use, given the higher rainfall total (and rainfall intensity) in this zone. For a tree canopy cover in the range 20–80 %, erosion rates were relatively low, but surface runoff increased to 36 to 62 % of rainfall. Differences in soil type influenced the thresholds, as the areas’ Inceptisols have lower intrinsic porosity than Andisols. A high soil surface roughness and litter thickness assist in reducing surface runoff and soil erosion. Where more open forms of agroforestry, with tree canopy cover less than 80 % are becoming more common this will affect water resources in the downstream area and increase vulnerability to climate change.